Kualitas Air Tanah dan Peta Sebaran Kualitasnya di Sekitar Tempat Pembuangan Akhir (TPA) Galuga - Sri Melianti Rahayu; Farid Ramadhan; Teti Syahrulyati; Sutanto, Sutanto (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The increasing population has resulted in a higher volume of waste at the Galuga landfill, generating leachate that potentially contaminates the surrounding shallow groundwater. Groundwater serves as a crucial source for domestic needs; thus, its contamination poses serious health risks and threatens ecological balance. This study aims to analyze the quality of shallow groundwater around the Galuga landfill and to map its spatial distribution as a foundation for sustainable environmental monitoring and management. The research methods included collecting groundwater samples from seven representative points along the groundwater flow direction, analyzing physical parameters (temperature, pH, turbidity), chemical parameters (Fe, Mn, NO₃⁻, and Cl⁻), and microbiological parameters (E. coli and total coliform), followed by calculating the Water Quality Index (WQI) using the NSF-WQI method. The findings revealed that several parameters, particularly Fe, Mn, E. coli, and total coliform, exceeded the permissible drinking water standards established by the Indonesian Ministry of Health Regulation No. 492/Menkes/Per/IV/2010. The average WQI score of 61.30 indicates a moderate water quality category. Therefore, it can be concluded that the shallow groundwater surrounding the Galuga landfill has been contaminated and is not suitable for direct consumption as drinking water. Consequently, it is recommended to implement more effective leachate management systems and conduct regular groundwater quality monitoring to prevent further contamination and safeguard community health and environmental sustainability.